The necessary dialogue for effective interdisciplinarity in Public health: contributions from Jünger Habermas’ s Communication theory - Araújo, Janieiry Lima de; Torres, Daniele Viana Maia; Silva, Kely Vanessa Leite Gomes da; Silveira, Lia Carneiro (Revista de Enfermagem UFPE on line, 2009)
ABSTRACT Objective: theoretical reflection on interdisciplinarity in the health system which considers dialogue as a structural tool in the public health practices which are aware, ethical and interactive. Methods: as an attitude towards the epistemologic object, we have attributed meaning to the concepts about sickness/health in a historical, social and cultura way; in relation to interdisciplinarity, its social, historical and theoretical aspects and its communicative way of acting in the public health, fundamental discussion based on the theory of communicative action by Jünger Habermas. Results: the interdisciplinarity in the public health is about overcoming the cristallized labour relations, the fragmented, the know-how and specialized aiming at achieving the stractegically elaborated objectives. Conclusion: the communicative action values the possibility of the actors participation, the reflexive and critical dialogues in relation to health problems, the development of methods of working which give priority to the discourse, the speeches, the linguistic consensus, the validity and truth, be it practical or theoretical, collectivelly built. Descriptors: health; communication; interdisciplinary. RESUMO Objetivo: reflexão teórica acerca da Interdisciplinaridade em Saúde que compreende o diálogo como ferramenta estrutural das práticas de saúde conscientes, éticas e interativas. Metodologia: como atitude de aproximação ao objeto epistemológico, dá-se significado aos conceitos de saúde-doença histórico-social e culturalmente construídos; da interdisciplinaridade, seus aspectos teóricos-históricos-sociais e do Agir Comunicativo em Saúde, discussão fundamentada na Teoria da Ação Comunicativa de Jünger Habermas. Resultados: a interdisciplinaridade em saúde postula superar a cristalização das relações de trabalho, do saber-fazer fragmentado e especializado com o objetivo de atingir metas estrategicamente elaboradas. Conclusão: o agir comunicativo em saúde valoriza a possibilidade da participação dos atores envolvidos, da existência de diálogos críticos e reflexivos quanto à problemática de saúde, da criação de método de trabalho que priorize o discurso, as falas dos indivíduos, o alcance do consenso linguístico, da validade e da verdade, seja teórica ou prática, construída coletivamente. Descritores: saúde; comunicação; interdisciplinar. RESUMEN Objetivo: reflexión teórica acerca de la interdisciplinaridad en sanidad que comprende el diálogo como herramienta estructural de las prácticas de sanidad conscientes, ética e interactivas. Metodología: como actitud de acercamiento al objeto epistemológico, hemos dado significado a los conceptos de sanidad-enfermedad histórico-social y culturalmente construído; de la interdisciplinaridad, sus aspectos teóricos-históricos-sociales y del actuar comunicativo en sanidad, discusión fundamentada en la teoría de la acción comunicativa de Jünger Habermas. Resultados: la interdisciplianaridad en sanidad propone superar la cristalización de las relaciones de trabajo, del saber-hacer fragmentado y especializado con el objetivo de lograr metas estratégicamente elaboradas. Conclusión: el actuar comunicativo en sanidad valora la posibildad de la participación de los actores, de la existencia de diálogos críticos y reflexivos cuanto a la problemática de la sanidad, de la creación de método de trabajo que de prioridad al discurso, las hablas de los indivíduos, el alcance del concenso lingüístico, de la validad y de la verdad, sea teórica o práctica, construída colectivamente. Descriptores: salud; comunicación; interdisciplinaria.